Project-Based Learning to Improve Statistical Application Literacy Competence of Economic Education Students - Rusdarti; Nina Farliana; Nina Oktarina (Economics Education Department Universitas Negeri Semarang, 2025)
This research aims to obtain an effective strategy for increasing students' statistical application literacy competency through Project-Based Learning (PjBL) in the Statistics Applications course. Research methods used experimental design, learning statistical applications using practical computer program software applications in a computer laboratory with the PjBL model. The control class teaches statistical applications without using projects, but is tasked with individually carrying out data processing practices. The research results show increased literacy competency in IT-based statistical applications or computer software in learning. The pre-test and post-test results for the experimental class, Sig 0.000 < 0.05, indicate a significant difference. The N-Gain result is 61.79 in the medium category. The level of motivation to learn statistical applications in the control group was 65.2% in the medium category, while the motivation in the experimental group was 82.67% in the high category. In this way, the PjBL model can increase motivation for literacy competency in statistical applications in economics education students. Students' literacy competency in statistical applications can increase; in the experimental class, the post-test score was obtained = 85.158, and they were skilled and able to use the mastered software creatively. Carry out continuous development of statistical application literacy by being innovative, creative, experienced, and competent to analyze data efficiently.